2023
DOI: 10.1186/s13018-023-03795-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between inflammatory markers and bone mineral density: a cross-sectional study from NHANES 2007–2010

Abstract: Purpose Monocyte-to-lymphocyte ratio (MLR), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) are acknowledged as novel inflammatory markers. However, studies investigating the correlation between inflammatory markers and osteoporosis (OP) remain scarce. We aimed to investigate the relationship between NLR, MLR, PLR and bone mineral density (BMD). Methods A total of 9054 participants from the National Health and Nutrition Exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…studied 290 postmenopausal women in Finland and found a connection between poor bone density, adipokines and vascular calcification ( 45 ). Second, systemic inflammation is also associated with levels of TG, HDL-C, and bone metabolism ( 46 , 47 ). For example, Huang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…studied 290 postmenopausal women in Finland and found a connection between poor bone density, adipokines and vascular calcification ( 45 ). Second, systemic inflammation is also associated with levels of TG, HDL-C, and bone metabolism ( 46 , 47 ). For example, Huang et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Varri et al studied 290 postmenopausal women in Finland and found a connection between poor bone density, adipokines and vascular calcification (45). Second, systemic inflammation is also associated with levels of TG, HDL-C, and bone metabolism (46,47). For example, Huang et al found that HDL-C levels were lower and TG levels were higher in the group with systemic lupus erythematosus (SLE), compared to the healthy control group; Ruaro et al found that BMD and trabecular scores were lower in SLE patients than in healthy matched controls (48,49).…”
Section: Discussionmentioning
confidence: 99%